Carbon nanotubes, but not spherical nanoparticles, block autophagy by a shape-related targeting of lysosomes in murine macrophages. Issue 8 (3rd August 2018) - Cohignac, Vanessa; Landry, Marion Julie; Ridoux, Audrey; Pinault, Mathieu; Annangi, Balasubramanyam; Gerdil, Adèle; Herlin-Boime, Nathalie; Mayne, Martine; Haruta, Masatake; Codogno, Patrice; Boczkowski, Jorge; Pairon, Jean-Claude; et al.
ABSTRACT: Nanoparticles (NPs) can be toxic, depending on their physico-chemical characteristics. Macroautophagy/autophagy could represent a potential underlying mechanism of this toxicity. We therefore set up a study aimed to characterize in depth the effects, on autophagy, of macrophage exposure to NPs, with a particular attention paid to the role of NP physico-chemical characteristics (specifically chemical composition, shape, size, length, crystal phase, and/or surface properties). We demonstrate that exposure to carbon nanotubes (CNT) but not to spherical NPs leads to the blockage of the autophagic flux. We further identified lysosomal dysfunction, in association with the downregulation of SNAPIN expression, as the underlying mechanism responsible for the CNT-induced autophagy blockade. These results identify for the first time the shape as a major determinant of the interaction of NPs with the autophagy pathway. Moreover, identifying the lysosomes and SNAPIN as primary targets of MWCNT toxicity opens new directions in the interpretation and understanding of nanomaterial toxicity.